Social adjustment of adolescents with hearing impairment in Nigeria: Will televised aggression and pornographic addiction mediate? - Adeniyi, Samuel Olufemi; Kuku, Olaotan Oladele (Specijalna edukacija i rehabilitacija, 2023)
Introduction. Living adaptively in any environment depends on several factors ranging from personal to environmental. In the event of development, there is the complexity that globalisation through digitalisation has added to adaptive living among youngsters, especially those living with hearing impairment. Objectives. This study investigated the effects of televised aggression and pornographic addiction on social adjustment of adolescents with hearing impairment in two states in South-west Nigeria. Methods. The study employed a descriptive survey study of expo facto type. Samples of 118 adolescent students with hearing impairment participated in the study through simple random and purposive sampling techniques. A Social Adaptation Inventory with a reliability of .79 was used to collect data from the respondents. Pearson Product Moment Correlation Coefficient and Multiple Regressions were used to test the hypotheses at .05 level of significance. Results. A significant relationship was found between televised aggression and social adjustment problems of adolescents with hearing impairment. Pornographic addiction has a significant relationship with social adjustment of adolescents with hearing impairment. Also, there were joint contributions of televised aggression and pornographic addiction to social adjustment of adolescents with hearing impairment in South-west Nigeria. Conclusion. Parents are admonished to monitor their adolescents with hearing impairment in a bid to censor the kinds of television programmes and print media materials they engage in because they also undergo the same developmental process as adolescents without hearing impairment.
Keywords: televised aggression; pornographic addiction; social adjustments; adolescents with hearing impairment